It’s Good to Be First: Order Bias in Reading and Citing NBER Working Papers - Feenberg, Daniel; Ganguli, Ina; Gaulé, Patrick; Gruber, Jonathan (The Review of Economics and Statistics, 2017)
When choices are made from ordered lists, individuals can exhibit biases toward selecting certain options as a result of the ordering. We examine this phenomenon in the context of consumer response to the ordering of economics papers in an e-mail announcement issued by the NBER. We show that despite the effectively random list placement, papers listed first each week are about 30% more likely to be viewed, downloaded, and subsequently cited. We suggest that a model of “skimming” behavior, where individuals focus on the first few papers in the list due to time constraints, would be most consistent with our findings.